2011
DOI: 10.1111/j.1447-0756.2011.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestation‐specific reference intervals for right and left ventricular ejection force from 12 to 40 weeks of gestation

Abstract: Fetal cardiac physiology can be studied and Doppler indices reliably measured as early as the late first trimester of pregnancy. Ventricular ejection force and its relationship with fetal growth could be explored in future studies and this may eventually provide better understanding of changes which may predispose to adult cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Similar finding were reported by Parasuraman et al . [ 3 ] and Russel et al . [ 10 ] Our study has also shown that the MPI has no correlation with either gestational age or heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar finding were reported by Parasuraman et al . [ 3 ] and Russel et al . [ 10 ] Our study has also shown that the MPI has no correlation with either gestational age or heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been particular interest in fetal myocardial performance index (MPI or Tei index) as it gives an evaluation of both systolic and diastolic ventricular functions. [ 3 ] In fetus though cardiac failure is less common, implementation of this technique helps in identifying subtle changes in cardiac function in subclinical phase. This in turn helps in identifying the high-risk population and their subsequent management.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are five reports on reference values of ejection forces of the cardiac chambers in the fetal period. [1112131415] In none of them, all the four cardiac chambers are simultaneously measured. Furthermore, there is no study on reference values of RAEF and LAEF during any week of gestation in healthy fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on ventricular ejection force in fetuses with normal and abnormal hearts, and the literature on fetal atrial ejection force is even scarcer. [1112131415] To the best of our knowledge, measurement and comparison of the ejection force of the four cardiac chambers of the normal fetal heart has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…RVO% could be measured in 20/26 (77%) of the patients with CDH and 17/23 (74%) of the patients with CPAM. Right ventricular ejection force [VEF(RV)] was calculated using the equation VEF(RV) = (1.055 × cross-sectional area of the pulmonary valve × velocity time interval during the acceleration phase) × (peak systolic velocity of the Doppler envelope/time to peak velocity) [20,21] and could be measured in 22/26 (85%) of the patients with CDH and 19/23 (83%) of the patients with CPAM.…”
Section: Methodsmentioning
confidence: 99%